Pengaruh Motivasi Kerja Dan Stres Kerja Terhadap Kinerja Pegawai Pada Balai Besar Meteorologi, Klimatologi, Dan Geofisika Wilayah II Tangerang Selatan - Intani Aulia; Nariah Nariah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the influence of work motivation and work stress on employee performance at the Center for Meteorology, Climatology and Geophysics Region II, South Tangerang, both partially and simultaneously. method used is quantitative. results of the t test research showed that the calculated t for work motivation was 5.770 > t table of 1.665 or a significance of 0.00 < 0.05, meaning that partially there was a significant influence of work motivation on employee performance. And the calculated t for work stress is -5.150 > t table 1.665 or a significance of 0.00 < 0.50, meaning that partially there is a significant influence of work stress on employee performance. For the f test, the calculated f is 34.312 > f table 3.15 or a significance of 0.000 < 0.05, meaning that simultaneously there is a significant influence of work motivation and work stress on employee performance. Multiple linear regression analysis obtained the equation Y = 40.569 + 0.250 (X1) - 0.217 (X2). The determination analysis obtained a value of 0.471 with a percentage of 47.1%, while the remaining 48.7% was caused by other variables. The results of the f test obtained a calculated f of 34.312 > f table 3.15 or a significance of 0.000 < 0.05, meaning that simultaneously there is a significant influence of work motivation and work stress on employee performance, and the coefficient of determination is 0.471. This illustrates that the variables Work Motivation (X1) and Work Stress (X2) have an influence of 47.1% on Employee Performance (Y), while the remaining 48.7% is caused by other variables not investigated in this research.